Effect of light supply on CO2 capture from atmosphere by Chlorella vulgaris and Pseudokirchneriella subcapitata - J. C. M. Pires (2014)
Carbon dioxide (CO2) is one of the primary greenhouse gases that contribute to climate change. Consequently, emission reduction technologies will be needed to reduce CO2 atmospheric concentration. Microalgae may have an important role in this context. They are photosynthetic microorganisms that are able to fix atmospheric CO2 using solar energy with efficiency ten times higher than terrestrial plants. The objectives of this study were: (i) to analyse the effect of light supply on the growth of Chlorella vulgaris and Pseudokirchneriella subcapitata; (ii) to assess the atmospheric CO2 capture by these microalgae; and (iii) to determine the parameters of the Monod model that describe the influence of irradiance on the growth of the selected microalgae. Both microalgae presented higher growth rates with high irradiance values and discontinuous light supply. The continuous supply of light at the highest irradiance value was not beneficial for C. vulgaris due to photooxidation. Additionally, C. vulgaris achieved the highest CO2 fixation rate with the value of 0.305 g-CO2 L1 d1. The parameters of the Monod model demonstrated that C. vulgaris can achieve higher specific growth rates (and higher CO2 fixation rates) if cultivated under higher irradiances than the studied values. The presented results showed that microalgal culture is a promising strategy for CO2 capture from atmosphere.